Online Attention of Uncited Articles in Information Science - Castanha, Rafael Gutierres; de Mira, Bianca Savegnago [UNESP]; Delbianco, Natalia Rodrigues [UNESP] (Universidad Nacional Autonoma de Mexico, 2024)
This report analyses the distribution of online attention received by uncited articles of Information Science (In-foSci). Specifically, it aims to understand citation evolution in conjunction with altmetric scores over the years of publication. As a methodology, 45 616 articles –published between 2012 and 2021 in the ‘Information Science & Library Science’ category in the Web of Science database (WOS)– were collected. The publication year, citations received in each article and their respective altmetric scores were extracted from this sample. Subsequently, descrip-tive statistical analyses –related to altmetric scores– were conducted based on the publication year. The difference in the proportion of articles without altmetric scores among citation classes was assessed using the Student’s T-test. Besides, the Mann-Whitney test was applied to examine whether there were significant differences between citation classes according to the year of publication based on altmetric scores. Results showed that, regardless of citation class and publication year, the most frequent altmetric score among articles is zero. In conclusion, there are altmetric differences between cited and uncited articles; uncited articles tend to receive less altmetric attention than those with citations. Additionally, altmetric attention is not distributed symmetrically, since there is a predominant frequency of zero across all analysed citation classes and years.
Atención en línea de artículos no citados en Ciencia de la Información
Atenção online de artigos não citados em Ciência da Informação
Keywords: Altmetric Attention Score; Altmetrics; Bibliometrics; Citation; Uncited